Calcifying odontogenic cyst associated with complex odontoma in the posterior litera of the maxilla. A case report and review of the literature - Larios-Parra, Jorge Luis (2022)
The calcifying odontogenic cyst (COC) is rare and represents <1% of all odontogenic cysts, it belongs to the lesions known as “ghost cell tumors”, these are a family of lesions that vary in clinical presentation of cyst or solid neoplasia, in their behavior biological from benign to locally aggressive or metastatic, this diversity has generated extensive debate on the classification, terminology, management and prognosis of these pathologies. We present the clinical case of a 17-year-old male patient with a diagnosis of calcifying odontogenic cyst associated with a complex odontoma located in the posterior region of the maxilla, in the literature there are only 27 reported cases of (COC) in that area, he was treated by surgical enucleation, curettage, rotation of the buccal fat pad and placement of titanium mesh to reconstruct the anterior wall of the maxillary sinus. The clinical and radiographic postoperative control at 12 months does not show recurrence of the lesion, in addition it exhibits an excellent functional and aesthetic result, this allows us to conclude that the treatment was adequate. We conducted a review of the literature in Science Direct, PubMed and Cochrane, in order to report the clinical, histopathological, radiographic characteristics and the treatment of these lesions.